Daktylus und Enhoplios in Damons Rhythmuslehre - Almazova, Nina (Hyperboreus, 2016)
In an obscure passage of Plato (Resp. 3. 400 a–c) Socrates refers to Damon’s rhythmic theory and mentions a “compound enoplian” and a “dactylic and heroic” rhythms. The same Damonian doctrine is probably implied in Aristophanes’ verse (Nub. 648–651), where the rhythms κατ’ ἐνόπλιον and κατὰ δάκτυλον are opposed. It follows from the context of Aristophanes that Damon’s studies were generally known, and that the named types of rhythms were similar, but at the same time well distinguishable according to a certain criterion. One can assume that rhythms consisting of pure dactylic feet belonged to the category κατὰ δάκτυλον, but it is disputable if spondees, acephalic and catalectic dactyls and dactyloepitrites were also included. On the other hand, it was argued that precisely the dactylo-epitrite cola – namely enoplian, prosodiac, hemiepes, and reizian – formed the κατ’ ἐνόπλιον category. A clear criterion, which Damon could have used to oppose these two species of rhythms, was proposed by K. J. Dover: he conjectured that κατὰ δάκτυλον were purely dactylic, anapaestic, and spondaic sequences, whereas κατ’ ἐνόπλιον were those in which a division into dactylic, anapaestic, or spondaic units was not possible without a “remainder” at the beginning or the end. The author tries to back up this hypothesis analyzing fragments which in the classical period could be considered as examples of dactylic category. In particular, it follows from Glaucus (Ps.-Plut. De mus. 1133 f) that τὸ κατὰ δάκτυλον εἶδος was a trait of traditional citharodic nomes, and Aristophanes (Ran. 1264–1277, 1284–1295) adduces examples of a rhythm which was typical for such nomes.As regards the ethos which Damon could ascribe to dactylic and enoplian rhythms, only the most cautious assumptions are possible. Probably the dactyl was associated with epic poetry and sacred hymns, and enoplian with armed dances. Pedagogical use of such dances is treated, on one hand, by Plato (Leg. 7. 795 d – 796 b), and on the other hand, by Athenaeus (14. 25, 628 c–f), who mentions Damon and expresses ideas reminding of Plato, so it is not excluded that both passages reﬂect Damon’s theory to some extend. One can suppose that enoplian was suitable for training manly and self-restrained behavior at war, and dactyl in peace (cf. the aims of education in Plat. Resp. 3. 399 a–c).